2022
DOI: 10.1371/journal.pone.0275155
|View full text |Cite
|
Sign up to set email alerts
|

Interbirth interval and maternal anaemia in 21 sub-Saharan African countries: A fractional-polynomial analysis

Abstract: Background Maternal anaemia is a global public health problem contributing to adverse maternal and perinatal outcomes. In addition to other risk factors, interbirth interval has been identified as a potentially modifiable risk factor of maternal anaemia. However, the current evidence for the association between interbirth interval and maternal anaemia remains inconclusive. Hence, this study examined the association between the interbirth interval and maternal anaemia in sub-Saharan Africa. Methods We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…For instance, it was found that the pooled prevalence of anemia among reproductive-age women in SSA countries was 40.5% (95% CI = 40.2%-40.7%), which was almost consistent with the previous study in East Africa that reported the prevalence ranging from 40.7% to 42.9% [ 23 ]. However, our finding was higher than the studies in 21 SSA countries (36.9%) [ 34 ], Ethiopia (37.5%) [ 21 ], Uganda (32%) [ 32 ], Rwanda (19%) [ 31 ], and Pakistan (18%) [ 22 ]. This discrepancy could be partly explained by differences in the scope of the study and population.…”
Section: Discussioncontrasting
confidence: 90%
“…For instance, it was found that the pooled prevalence of anemia among reproductive-age women in SSA countries was 40.5% (95% CI = 40.2%-40.7%), which was almost consistent with the previous study in East Africa that reported the prevalence ranging from 40.7% to 42.9% [ 23 ]. However, our finding was higher than the studies in 21 SSA countries (36.9%) [ 34 ], Ethiopia (37.5%) [ 21 ], Uganda (32%) [ 32 ], Rwanda (19%) [ 31 ], and Pakistan (18%) [ 22 ]. This discrepancy could be partly explained by differences in the scope of the study and population.…”
Section: Discussioncontrasting
confidence: 90%
“…A short inter-pregnancy interval is said to hinder the restoration of the depleted maternal resources that are needed for the subsequent pregnancy and pose the risk of anemia, pregnancy-induced hypertension, premature rapture of the membranes, and others [40] Several observational studies have confirmed the association between the short inter-pregnancy interval and anemia. [40–42] Moreover, this study found that about 41.7% of pregnant women had a short inter-pregnancy interval. This raises concerns about family planning use among women of reproductive age in this setting, owing to the potential effect of a short inter-pregnancy interval on anemia.…”
Section: Discussionmentioning
confidence: 81%
“…Maternal anemia always related to higher risk of disadvantageous events related to birth and or health outcomes [47,48]. In parts of Africa [49,50], south Asia [48,51], and many more LMICs [52] actually had a higher merged anemia prevalence than did other Asian and upper-middle-income countries. Overall, in LMICs, 12% of low birth weight, 19% of preterm births, and 18% of perinatal mortality were related to maternal anemia [47].…”
Section: Fig 1 Box Plot Diagram Regarding Birth Weight Based On Gende...mentioning
confidence: 99%